Pengaruh Cutting Speed dan Laser Power Proses Fiber Laser Cutting Terhadap Kekasaran Permukaan Pada Baja AISI 1040 Dengan Ketebalan 6mm - Rahmadianto, Febi; Pohan, Gerald A.; Yanuar, Kenzha (Jurnal Teknik, 2025)
Surface roughness is a measure of microscopic irregularities on a material's surface that affects the performance, service life, and aesthetics of a product. This study analyzes the effect of cutting speed and Laser Power in the fiber Laser Cutting process on the surface roughness of 6 mm thick AISI 1040 steel. The method used was true experimental research with variations in cutting speed (500, 1000, 1500 mm/min) and Laser Power (80%, 90%, 100%). The results show that the combination of 1000 mm/min cutting speed and 80% Laser Power produced the lowest roughness of 2.3 µm, while the combination of 500 mm/min and 90% produced the highest roughness of 29.36 µm. Increasing Laser Power generally increases roughness, except at 100% Laser Power with 500 mm/min cutting speed which decreased due to more uniform material melting. The conclusion of this study is that optimal parameters (cutting speed 1000 mm/min and Laser Power 80%) produce a smooth surface. These findings can be a reference for the manufacturing industry in improving product quality through Laser Cutting process optimization.